(untitled) (Research Nepal Journal of Development Studies, 2020)
Normally, people note that Kapilavastu is the birthplace of Lord Gautam Buddha, but it is also the birth place of great previous Buddhas. An analysis of Buddhas of Kapilavastu Nepal from tourism perspective is a study of birthplaces of three prominent Buddhas. The main objective of the study is to find out the general information of the historical birthplaces of Buddhas of Kapilvastu. The study is based in literature review and secondary information. These places are full of tourism potentiality and historical significance. Governments are advised to make sound tourism development master plan of the sacred birthplace of Kapilmuni, Krakukchhanda, Kanakmini and Shakyamuni Buddhas.